ANALISIS KOEFISIEN PRODUKTIVITAS TUKANG KAYU PADA PEKERJAAN BEKISTING BALOK ANAK PROYEK PEMBANGUNAN GUDANG - Kartika Hapsari; Naurah Nabihah (Universitas Widyatama, 2025)
Labor productivity is the ability of construction workers to complete their main tasks and functions according to their respective fields. Many factors influence labor productivity, including time and work methods. This study aims to compare the actual productivity coefficient of carpenters with the Permen PUPR standards for formwork beam tasks in the Cakung Modern Logistic Warehouse project and identify the main factors affecting labor productivity in these tasks. The data collection methods used in this study are work sampling for productivity coefficient through field observation and questionnaires to determine the factors most affecting the productivity of carpenters in formwork beam tasks. The questionnaires data were then processed using IBM SPSS. The result of study show that the comparison of the actual coefficient with the Permen PUPR is 0,314610 for forwork scaffolding, 0,110432 for formwork fabrications, 0,006074 for formwork installation, and 1,636526 for formwork dismantling. The three main factors affecting the productivity of carpenters in forwok beam tasks are rainfall, work methods, and design complexity